GCM: a grid configuration manager for heterogeneous grid environments. (17th May 2005) - Lindner, Peggy; Gabriel, Edgar; Resch, Michael M.
Deploying grid technologies by distributing an application over several machines is widely emerging for large scientific simulations. While in the last couple of years distributed simulations were often executed on a pure demonstration level, currently ongoing work is focusing on taking the steps necessary to use the technology in an everyday production environment. This paper presents the Grid Configuration Manager (GCM), a tool developed to hide the complexity and ease the handling of scientific, computational jobs in heterogeneous grid environments, by abstracting the necessary tasks and implementing them for the most widespread grid middleware (Globus, UNICORE) and traditional access mechanism (SSH).